Detection of granulocyte‐reactive antibodies: a comparison of different methods. Issue 3 (30th December 2014) - Heinzl, M. W.; Schönbacher, M.; Dauber, E.‐M.; Panzer, S.; Mayr, W. R.; Körmöczi, G. F.
<x xml:space="preserve">Abstract</x> Background and Objectives Granulocyte‐reactive antibodies can cause autoimmune and neonatal immune neutropenias as well as transfusion‐related acute lung injury. The classical antibody‐detection methods granulocyte aggregation test (GAT), granulocyte immunofluorescence test (GIFT) and monoclonal antibody‐specific immobilization of granulocyte antigens (MAIGA) are time‐consuming and technically challenging. In recent years, flow cytometric white blood cell immunofluorescence test (Flow‐WIFT) and the microbeads assay LabScreen® Multi have emerged and are still subject of evaluation. These serological tests were compared on a screening and specification level. Materials and Methods For screening, the combination of GAT/GIFT was compared to Flow‐WIFT testing 333 samples. Positive samples were further analysed with MAIGA and LabScreen® Multi. Results Granulocyte aggregation test/GIFT detected 77 positive samples, Flow‐WIFT found 108 granulocyte‐reactive samples. Six Samples were only positive in GAT/GIFT, and 37 samples were only positive in Flow‐WIFT (κ = 0·682). Antibody specification with MAIGA and the microbeads assay confirmed granulocyte‐reactivity in 83 cases with 70 matching results (κ = 0·742). However, out of six detected human neutrophil antigen (HNA) reactivities only two specificities matched in both assays. Conclusion Flow‐WIFT may be a valuable addition to GIFT for granulocyte‐reactive antibody screening. MAIGA remains the most reliable laboratory method for antibody specification.